How to preserve brewer s grain? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Godfrey Ssentongo, managing director of Modern Farming Systems, PO Box 5013, Jinja, Uganda (fax: + 256 43 12 15 60) asks for help in keeping brewer s grain. 'This grain, also known as brewer s mash (a by-product from beer factories) is the...